2021
DOI: 10.3389/fcvm.2021.814402
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Circular RNA in Aortic Vascular Tissues of Spontaneously Hypertensive Rats

Abstract: Background: Circular RNAs (circRNAs), as a kind of endogenous non-coding RNA, have been implicated in ischemic heart diseases and vascular diseases. Based on theirs high stability with a closed loop structure, circRNAs function as a sponge and bind specific miRNAs to exert inhibitory effects in heart and vasculature, thereby regulating their target gene and protein expression, via competitive endogenous RNA (ceRNA) mechanism. However, the exact roles and underlying mechanisms of circRNAs in hypertension and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Primary hypertension is a common chronic disease that usually causes other health complications, such as coronary artery disease, stroke, renal failure and heart failure, and poses a great threat to human health (89,90). Currently, the relationship between miR-34a and hypertension is relatively limited (91).…”
Section: Roles Of Mir-34a In Hypertensionmentioning
confidence: 99%
“…Primary hypertension is a common chronic disease that usually causes other health complications, such as coronary artery disease, stroke, renal failure and heart failure, and poses a great threat to human health (89,90). Currently, the relationship between miR-34a and hypertension is relatively limited (91).…”
Section: Roles Of Mir-34a In Hypertensionmentioning
confidence: 99%
“…Compared to the low-level threshold with score >140 and energy < −10 in miRanda prediction, our study employed a threshold with score >180 and energy < −30 for the highest accuracy and confidence in the prediction of circRNA-miRNA interactions ( Li et al, 2018b ; Li et al, 2019b ; Li et al, 2020 ; Cao et al, 2021 ). Similarly, the miRNA-mRNA interactions identified by ≥ 6 databases and miRDB score ≥80 are supposed to be different, to some extent, from those obtained by one to three databases ( Li et al, 2019b ; Cao et al, 2021 ; Liu et al, 2021 ). Although the circRNA-miRNA and miRNA-mRNA interactions were of high confidence, in vivo and/or in vitro investigation will be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al, [24] found 485 differentially expressed circRNAs in aortic vascular tissue of spontaneously hypertensive rats (SHR) when compared to Wistar Kyoto (WKT) rats. Three circRNA-miRNA-mRNA axes were predicted and later confirmed in SHR aortas, regulating the NOTCH1, FOXO3, and STAT3 genes, all of which are involved in vascular diseases.…”
Section: Circrnas In Arterial Hypertensionmentioning
confidence: 99%